Observation Bias: The Impact of Demand Censoring on Newsvendor Level and Adjustment Behavior - Rudi, Nils; Drake, David (Management Science, 2014)
In an experimental newsvendor setting, we investigate three phenomena: level behavior—the decision maker's average ordering tendency; adjustment behavior—the tendency to adjust period-to-period order quantities; and observation bias—the tendency to let the degree of demand feedback influence order quantities. We find that, in three of four conditions, the portion of mismatch cost that results from adjustment behavior exceeds the portion of mismatch cost caused by level behavior. Observation bias is studied through censored demand feedback, a situation that arguably represents most newsvendor settings. When demands are uncensored, subjects tend to order below the normative quantity when they face high margin and above the normative quantity when they face low margin, but in neither case do they order beyond mean demand (the pull-to-center effect). Censoring in general leads to lower quantities, magnifying the below-normative-level behavior when they face high margin but partially counterbalancing the above-normative-level behavior when they face low margin, violating the pull-to-center effect in both cases. Data, as supplemental material, are available at http://dx.doi.org/10.1287/mnsc.2013.1825 . This paper was accepted by Christian Terwiesch, operations management.